Bone health in transgender assigned female at birth people: effects of gender-affirming hormone therapy and gonadectomy - Sanna, Elena; Lami, Alessandra; Giacomelli, Giulia; Alvisi, Stefania; Paccapelo, Alexandro; Seracchioli, Renato; Meriggiola, Maria Cristina (Frontiers in Endocrinology, 2024)
Introduction -Gender affirming hormone therapy (GAHT) and gender affirming surgery (GAS) may be desired by transgender and gender diverse (TGD) individuals who want to affirm their gender identity. Testosterone is the basis of GAHT for transgender individuals assigned female at birth (AFAB), while GAS can involve hysterectomy, bilateral salpingectomy, bilateral oophorectomy (BO), thorax masculinization and phalloplasty. Our study aimed to evaluate the effects of GAHT on the bone health of TGD AFAB individuals who have undergone or not undergone BO.Methods -This was a single-center, longitudinal study with retrospectively collected data. TGD AFAB GAHT-naïve individuals were enrolled and underwent dual Xray absorptiometry scans and laboratory tests (hormonal, bone metabolism parameters) at baseline and after 5 and 10 years of GAHT.Results -Two hundred and forty-three TGD AFAB people were included in this study. Seventy-five subjects had completed data for 5 years and 19 subjects for 10 years of GAHT. At baseline, low bone density (Z-score < -2.0) was found in 2.5% (6/243) of subjects for lumbar spine (LS) while total hip (TH), femoral neck (FN) Z-scores and laboratory tests were within the normal female range. After stratifying by physical activity, the physically active group showed significantly higher LS BMD and Z-scores (p≤0.05). Five years after the start of GAHT, a significant reduction in LS (p≤0.05), TH (p≤0.001) and FN (p≤0.01) Z-scores was detected. A significant reduction in the Z-scores of all three bone sites was observed only in the subgroup that had undergone BO. After 5 years of GAHT, estradiol levels were significantly decreased compared to baseline (p≤0.001). Significantly higher estradiol levels were detected in the 5-year no-BO subgroup compared to the 5-year BO subgroup (p≤0.001). A significant reduction in LS and TH Z-scores were observed after 10 years of GAHT. At this time, estradiol levels were significantly decreased compared to baseline (p≤0.01).Bone density in TGD AFAB individuals is comparable to their peers prior to GAHT and BO but those subjects who underwent BO had a reduced Z-score at LS, FN, and TH after 5 years and at LS after 10 years of GAHT.